SENGKETA ANTARA INDONESIA DENGAN TIMOR LESTE DI KAWASAN NAKTUKA - Yohanes Arman; Servasius T Seran, Maria Stellamaris Werena Tupen, Maria Andriani Rosari Corebima (JOURNAL OF LAW AND NATION, 2024)
The determination of state boundaries with opposing countries or adjacent countries certainly needs to be resolved immediately. Likewise with the State of Indonesia which is a land-based country. Determination of maritime boundaries will have consequences for the jurisdiction, sovereign rights and sovereignty of a country. Likewise, with the determination of land boundaries between the State of Indonesia and the State of Timor Leste in the Naktuka Area, a series of actions or steps need to be taken that lead to resolving the dispute, considering that the Naktuka Area is included in the Sovereignty of the State of Indonesia and on the other hand the State of Timor Leste has taken deviant actions.